Nuclear calcium signaling induces expression of the synaptic organizers Lrrtm1 and Lrrtm2 - Hayer, Stefanie Nicole; Bading, Hilmar (The journal of biological chemistry, 2015)
Calcium transients in the cell nucleus evoked by synaptic activity in hippocampal neurons function as a signaling end point in synapse-to-nucleus communication. As an important regulator of neuronal gene expression, nuclear calcium is involved in the conversion of synaptic stimuli into functional and structural changes of neurons. Here we identify two synaptic organizers, Lrrtm1 and Lrrtm2, as targets of nuclear calcium signaling. Expression of both Lrrtm1 and Lrrtm2 increased in a synaptic NMDA receptor- and nuclear calcium-dependent manner in hippocampal neurons within 2-4 h after the induction of action potential bursting. Induction of Lrrtm1 and Lrrtm2 occurred independently of the need for new protein synthesis and required calcium/calmodulin-dependent protein kinases and the nuclear calcium signaling target CREB-binding protein. Analysis of reporter gene constructs revealed a functional cAMP response element in the proximal promoter of Lrrtm2, indicating that at least Lrrtm2 is regulated by the classical nuclear Ca2+/calmodulin-dependent protein kinase IV-CREB/CREB-binding protein pathway. These results suggest that one mechanism by which nuclear calcium signaling controls neuronal network function is by regulating the expression of Lrrtm1 and Lrrtm2.